The AIRE G228W mutation disturbs the interaction of AIRE with its partner molecule SIRT1 - Santos, Jadson C.; Dametto, Mariangela; Masson, Ana Paula; Faça, Vitor M.; Bonacin, Rodrigo; Donadi, Eduardo A.; Passos, Geraldo Aleixo (Frontiers in Immunology, 2022)
The autoimmune regulator (AIRE) protein works as a tetramer. It interacts with partner proteins to form the “AIRE complex” that pushes RNA Pol II stalling in the chromatin of medullary thymic epithelial cells. AIRE is the primary transcriptional controller in mTECs, promoting the expression of a large set of peripheral tissue antigen (PTA) genes in the thymus, which are implicated in the negative selection of auto aggressive thymocyte clones before they reach the periphery. Under normal conditions, the SIRT1 protein temporarily interacts with AIRE and deacetylates K residues of the AIRE SAND domain. Once the AIRE SAND domain is deacetylated, the binding with SIRT1 is undone, allowing the AIRE complex to proceed downstream. Considering that the in silico and in vitro binding of the (AIRE) SAND domain with SIRT1 provides a powerful model system for studying the dominant SAND G228W mutation mechanism, which causes the autoimmune APS-1 syndrome, here, we integrated computational molecular modeling, docking, dynamics between the whole SAND domain with SIRT1, and surface plasmon resonance using a peptide harboring the aminoacid residues 211 to 230 of SAND, to compare the structure and energetics of binding/release between AIRE G228 (wild-type) and W228 (mutant) SAND domain to SIRT1. We observed that the G228W mutation in the SAND domain negatively influences the AIRE-SIRT1 interaction. The troubled interaction might cause a disturbance in the binding of the AIRE SAND domain with the SIRT1 catalytic site, making it difficult for the AIRE complex to proceed downstream.